Canadian Helicobacter pylori Consensus Conference Update: Infections in Adults. (1st April 1999) - Hunt, RH; Fallone, CA; Thomson, ABR; Canadian Helicobacter Study Group,
Abstract : The first Canadian Helicobacter pylori Consensus Conference took place in April 1997. The initial recommendations of the conference were published in early 1998. An update meeting was held in June 1998, and the present paper updates and complements the earlier recommendations. Key changes included the following: the recommendation for testing and treating H pylori infection in patients with known peptic ulcer disease was extended to testing and treating patients with ulcer-like dyspepsia; it was decided that the urea breath test (not serology) should be used for routine diagnosis of H pylori infection unless endoscopy is indicated for another reason; and recommended therapies were a twice daily, seven-day regimen of a proton pump inhibitor (omeprazole 20 mg, lansoprazole 30 mg, pantoprazole 40 mg) or ranitidine bismuth citrate 400 mg, plus clarithromycin 500 mg and amoxicillin 1000 mg, or plus clarithromycin 500 or 250 mg and metronidazole 500 mg. The need was reiterated to have funding for readily accessible, accurate testing for H pylori infection with the urea breath test. It was strongly recommended that regional centres be established to monitor the prevalence of antibiotic-resistant H pylori infections. The initial consensus document referred to pediatric issues that were not addressed in this update but were the subject of a subsequent Canadian Helicobacter Study Group meeting, and will be published later in 1999.